Makna Komunikasi Non Verbal Dalam Tradisi Sarungan - Ananta, Pinka Erly (Mekomda: Media Komunikasi Dakwah, 2023)
This study has various objectives, the main purpose of this study is to analyze how the meaning of non-verbal communication in the sarong tradition at the Al-Kamal Integrated Islamic Boarding School Blitar. This study was designed to answer the above problems, so this study has a sub focus on the following: Behavior in the sarong tradition, space and time. The sub focus is used to measure the focus of this study entitled The meaning of non-verbal communication in the sarong tradition at the Al-Kamal Integrated Islamic Boarding School Blitar. The research approach is qualitative with a descriptive study. The results showed that: 1. The meaning of behavior in the sarong tradition as moral responsibility, courtesy, a symbol of modest living, a form of resistance to the incessant penetration of western culture. The santri also wear fragrances as a form of obeying the advice of the Prophet Muhammad SAW. 2. The meaning of Space and Time, that students wearing gloves are mandatory during their main activities, and are recommended when traveling outside the pesantren